STUDI EXPERIENCED REGRET, RISK TOLERANCE, OVERCONFIDANCE DAN RISK PERCEPTION PADA PENGAMBILAN KEPUTUSAN INVESTASI - Dewi Ayu Wulandari; Rr. Iramani (STIE Perbanas Surabaya, 2014)
Nowadays Investors often make investment decision irrationally. The decision is often based on their judgment that is far away from rational assumption. When investors face risky situation, there are some objectivities, emotions, and other psychological factors that usually effecttheir decision making. This purpose of study is to examine the effect of experienced regret, risk tolerance, overconfidence and risk perception on investment decision making among lecturers in economics studies in Surabaya. Sample of this study is the lecturers of the economics studies in Universities in Surabaya who are also the investors. This study usedpurposive, convenience and snow-ball sampling method. There are 72 respondents taken from questionnaire by survey method. To test hypotheses, this study employs descriptive analysis and multiple regression analysis. Moreover, by performing multiple regression analysis, this study found that only risk tolerance and risk perception have significant effect on investment decision making, but experienced regret, and overconfidence do not.